2018
DOI: 10.2298/bah1801001g
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the proportion of extractable and bound condensed tannins in birdsfoot trefoil (Lotus corniculatus) and sainfoin (Onobrychis viicifolia) during wilting, ensiling and pelleting processes

Abstract: Condensed tannins (CT) in legume forages vary not only in concentration and structure, but also in the portion of soluble and protein-and fibre-bound fractions. This study aimed to assess the changes in the total CT level as well as relative abundance of the three CT fractions from fresh to wilted, ensiled or pelleted legumes like in birds foot trefoil (two cultivars) and in sainfoin (one cultivar). Each legume underwent three consecutive harvests, of which the first two were wilted. Additionally, wilted legum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(50 reference statements)
3
10
0
3
Order By: Relevance
“…The contents of soluble and insoluble PAs in the different samples are presented in Figure 2 . Sainfoin had on average six-fold greater PA contents in fresh, wilted and silage materials than birdsfoot trefoil, which is in agreement with previous experiments [ 36 , 37 ]. During the conservation process of sainfoin, the total PA content (soluble and insoluble) was reduced by 29% in the silage compared with fresh and wilted samples.…”
Section: Resultssupporting
confidence: 92%
“…The contents of soluble and insoluble PAs in the different samples are presented in Figure 2 . Sainfoin had on average six-fold greater PA contents in fresh, wilted and silage materials than birdsfoot trefoil, which is in agreement with previous experiments [ 36 , 37 ]. During the conservation process of sainfoin, the total PA content (soluble and insoluble) was reduced by 29% in the silage compared with fresh and wilted samples.…”
Section: Resultssupporting
confidence: 92%
“…We found that most of the CT in the BT silage were bound to protein (54.8%), whereas the fiber-bound CT fraction represented the minor component (8.9%), with intermediate values for the soluble portion (35.8%). It is generally recognized that conservation methods, such as ensiling, reduce the extractability of CT and increase the insoluble portion of CT, with no effect on the total CT [ 33 ]. This is probably due to the partial disruption of plant cells as a result of physical chopping before ensiling, as well as due to the microbial fermentation that occurs during ensiling, which enables CT to react with other plant fractions and leads to an increase in the bound CT fraction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, Rufino-Moya et al (2019b) encontraron una reducción de los TCL y TCF al final de la floración respecto al estado vegetativo, mientras que no se encontraron diferencias en los TCP. En cambio, Girard et al (2018) no encontraron ningún cambio en las distintas fracciones de los TC cuando compararon esparceta en estado vegetativo, en plena floración y al final de la misma.…”
Section: Efecto Del Estado Fenológico De La Esparceta Sobre El Contenunclassified
“…La interacción de los TC con las proteínas del forraje en el silo reduce la proteólisis que tiene lugar durante el proceso de ensilado, resultando una mejora de la calidad del silo (Theodoridou et al, 2012). Los efectos del ensilado sobre los TC y sus fracciones están determinados por la variedad del forraje (Lorenz et al 2010), el estado fenológico (Girard et al, 2018) y/o el picado del forraje previo a su conservación (Scharenberg et al, 2007a;Girard et al, 2018). Generalmente, las fracciones de los TC varían más que los TCT, reduciéndose los TCL (45-77 %) en favor de los TCP y/o TCF (Scharenberg et al, 2007a;Lorenz et al, 2010;Girard et al, 2018;Rufino-Moya et al, 2019a).…”
Section: Efecto Del Estado Fenológico De La Esparceta Sobre El Contenunclassified
See 1 more Smart Citation